2014
DOI: 10.7150/ijms.9975
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Training Effect on Physical Performance and Obesity in Mice

Abstract: The purpose of this study was to verify the beneficial effects of whole-body vibration (WBV) training on exercise performance, physical fatigue and obesity in mice with obesity induced by a high-fat diet (HFD). Male C57BL/6 mice were randomly divided into two groups: normal group (n=6), fed standard diet (control), and experimental group (n=18), fed a HFD. After 4-week induction, followed by 6-week WBV of 5 days per week, the 18 obese mice were divided into 3 groups (n=6 per group): HFD with sedentary control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 35 publications
(42 reference statements)
3
37
0
3
Order By: Relevance
“…Moreover, WBV has been confirmed as potential alternative exercise training method to increase physical fitness adherence in non-obese [11] and obese adults [10]. As previously reported, WBV might have positive acute and chronic effects in both obese mice [30] and humans [28,10]. Huang et al [30] showed that WBV could improve exercise performance and prevent fat accumulation in obese mice suggesting a possible clinical use of WBV in the prevention and treatment of obesity.…”
Section: Salivary Cortisol Levelsmentioning
confidence: 87%
“…Moreover, WBV has been confirmed as potential alternative exercise training method to increase physical fitness adherence in non-obese [11] and obese adults [10]. As previously reported, WBV might have positive acute and chronic effects in both obese mice [30] and humans [28,10]. Huang et al [30] showed that WBV could improve exercise performance and prevent fat accumulation in obese mice suggesting a possible clinical use of WBV in the prevention and treatment of obesity.…”
Section: Salivary Cortisol Levelsmentioning
confidence: 87%
“…A recent study also with C57BL/6 mouse models pointed that MV can positively affect the body weight of animals (Huang et al. ).…”
Section: Discussionmentioning
confidence: 96%
“…One of the earliest reports of MV influence on obesity in a high-fat diet-induced obesity model (C57BL/6 mice) demonstrated that 12 weeks of treatment was able to reduce subcutaneous and visceral fat in the obese animals concurrent with increased bone marrow MSCs with decreased adipogenic differentiation capability (Luu et al 2009). A recent study also with C57BL/6 mouse models pointed that MV can positively affect the body weight of animals (Huang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…175 Vibration treatment was also tested and proved positive in a more severe obesity model. Application of vibration (0.5 × g , 45 Hz, 60 min/day) for 12 weeks in female db/db mice ameliorated insulin resistance, showing the potential for the treatment of type 2 diabetes.…”
Section: Combating Obesity With Mechanical Signalsmentioning
confidence: 99%
“…70,174 Whole-body vibration of different intensity but relatively low magnitude (0.13-0.68 × g, 5.6-13 Hz) was shown to improve exercise performance and reduce fatigue while also preventing fat accumulation in obese mice. 175 Vibration treatment was also tested and proved positive in a more severe obesity model. Application of vibration (0.5 × g, 45 Hz, 60 min/day) for 12 weeks in female db/db mice ameliorated insulin resistance, showing the potential for the treatment of type 2 diabetes.…”
Section: In Models Of Obesitymentioning
confidence: 99%